Neural representation of the decisional reference point in monkeys - Duc Nguyen; Erin L. Rich; Joni D. Wallis; Kenway Louie; Paul W. Glimcher (Proceedings of the National Academy of Sciences, 2025)
The decisional reference point serves as a hidden benchmark for evaluating options in decision-making. Despite extensive behavioral evidence for the existence of the reference point, its neural instantiation remains unclear. To identify reference point encoding at both the single-neuron and population levels, we analyzed neural activity from macaques performing a wealth accumulation task that dissociated objective reward values from the reference point. Across six frontal regions, we found that reference-related signals were broadly distributed at the single-neuron level. However, at the population level, only the ventral bank of the anterior cingulate cortex (vbACC) encoded the reference point significantly. In contrast, the dorsal bank of ACC and dorsolateral prefrontal cortex showed population-level encoding of reference-dependent subjective value signals. The temporal sequence of these signals and their known anatomical connectivity hints at a dedicated neural circuit for reference dependence, with the vbACC potentially serving as a global source of reference point signal modulating activity in downstream value-encoding regions.